Application of smart technologies in water management analysis - Gintarė Piaseckienė; Jurgita Antuchevičienė (Mokslas: Lietuvos Ateitis)
More and more regions of the world are suffering due to urbanization and emerging industries. Therefore, water extraction and water management become a priority issue globally. Scientists are beginning to implement the most modern technologies and use sustainable development and sustainable construction solutions which would help solve water management problems. The article analyses the application of the most advanced technologies in water management, which increase the efficiency of buildings in the operational phase and help to implement the goals of sustainable development and sustainable construction. The study found that AI (Artificial Intelligence) and IoT (Internet of Things) technologies can be applied in many areas of water management. For example, monitoring and prevention of engineering network accidents, water distribution in engineering networks, wastewater treatment, water desalination processes, selection of efficient water-saving engineering solutions, flood prevention and implementation of sustainable construction. The implementation of the most modern technologies benefit citizens, state institutions, water management companies and the ecosystem.